Fjordparken : en studie om postindustriell stadsomvandling - Persson, Mikaela (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2020)
Traces of industrialization can now be found in the ports of several coastal cities and have been gaining increasing focus in various planning discourses. The aim is to determine how to create better use of the land while weaving its existing qualities in as part of the existing cities, as the challenge in some of these transformation projects is that modern ports often have similar structures and cultural themes, regardless of the areas’ geographical locations and shapes. In this thesis, I studied interpretations of the concept of site, as well as sitespecific transformations regarding postindustrial port areas. The thesis begins with a literature review that investigates the different interpretations and how these can be used in a transformation process. The theoretical background focuses on the concept of site and the site as a complex situation that includes dynamic material and immaterial aspects. Based on the theoretical background, relevant methods were selected and used to analyze a real case in a case study. The chosen location is Fjordparken in Filipstad, Oslo, which is a postindustrial port area that the municipality plans to transform into part of the city center. The site analysis was conducted to establish how sitespecific properties can be identified and used practically in a design proposal. Indeed, the result of the analysis identified Filipstad’s challenges and opportunities that further form the basis for a design proposal. The collected empirical material was tested in practice in the design proposal to assess how it is possible, based on sitespecific theories, to transform Filipstad into a part of central Oslo. The proposal can be considered a vision of how Fjordparken could contribute to the municipality’s current plan proposal for all of Filipstad. The thesis concludes with a discussion of the thoughts, questions, and conclusions that emerged in the case study. Sitespecific design is so much more than focusing on preserving the material. That the immaterial aspects are also an important aspect is a valuable lesson from this work that I will take with me further into my profession as a landscape architect.